Viscous flow activation energy adaptation by isochronal spark plasma sintering. (1st January 2017) - Paul, Tanaji; Harimkar, Sandip P.
Abstract: The densification mechanism of amorphous Fe48 Cr15 Mo14 Y2 C15 B6 alloy powder during isochronal spark plasma sintering was analyzed to determine the innate function of high heating rates. Densification ensued and concluded at gradually lower temperatures while attaining higher maximum rates with increasing heating rates in the first stage. The shrinkage behavior analyzed under the theoretical framework of viscous flow revealed a steady reduction in the activation energy leading to a resultant enhancement of densification rate in the initial stage. Graphical abstract: